RISK MITIGATION STRATEGIES IN GLOBAL SUPPLY CHAINS: A LITERATURE REVIEW - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study examines risk mitigation strategies implemented in global supply chains through a comprehensive literature review. By identifying the best practices and most effective approaches, this study reveals that diversification of suppliers and resources, the use of advanced technologies such as big data, IoT, and blockchain, as well as the development of contingency plans and continuous audits are key pillars in managing supply chain risks. The implementation of these strategies not only increases a company's operational flexibility and transparency, but also enables faster and more accurate responses to potential disruptions, thus ensuring operational resilience and sustainability in the face of dynamic global challenges.